The wolf at the door: undue influence and elder financial abuse - Hackard, Michael (Hackard Global Media, 2017)
"In THE WOLF AT THE DOOR, veteran California attorney and elder financial abuse writer Michael Hackard draws from forty years of legal experience to advise families, caregivers, and professionals who work with seniors what elder financial abuse is, how to identify it, and--most importantly--what to do if abuse is suspected. As the baby boomer generation rapidly ages into retirement, elder financial abuse threatens to become a national epidemic. If not addressed early and aggressively, this unique form of exploitation can tear families apart, leaving shattered relationships and depleted bank accounts in its wake. You may not be able to prevent elder financial abuse from happening, but THE WOLF AT THE DOOR will empower you to fight back before it's too late. Concise and chock-full of practical information, THE WOLF AT THE DOOR is a must-have reference for anyone interested in learning about elder financial abuse and what can be done to combat it. The book is written for a general audience, and it offers case studies, research, and hard-won observations gleaned from a long career representing abuse victims and their loved ones. An index and compact sections make navigation easy, and dozens of endnotes direct readers to additional information about elder abuse, undue influence, estate planning and trusts, and more. The net profits from the sale of each copy of THE WOLF AT THE DOOR will be donated to the Alzheimer's Foundation of America."--Publisher's description